2016
DOI: 10.1038/srep29602
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Relationship between Sulphation Patterns and Conformation of Iduronic Acid in Heparan Sulphate

Abstract: The L-iduronic acid (IdoA) residue is a critically important structural component in heparan sulphate polysaccharide for the biological functions. The pyranose ring of IdoA is present in 1C4-chair, 2SO-skew boat, and less frequently, in 4C1-chair conformations. Here, we analyzed the conformation of IdoA residue in eight hexasaccharides by NMR. The data demonstrate a correlation between the conformation of IdoA and sulphations in the surrounding saccharide residues. For the 2-O-sulpho IdoA residue, a high degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
90
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 43 publications
12
90
0
Order By: Relevance
“…In the present study, the impact of 3- O -sulfation on the conformation of neighboring IdoA2S residues was investigated. The conformational analysis was completed by NMR through measuring the three bond proton proton coupling constants ( 3 J H-H ) 30 . The 3- O -sulfation increases the population of 2 S O conformer of the IdoA2S residue in hexasaccharides (compound 1 to 3 , Table 1 and Fig 1A), compared to that of the IdoA2S residue in a hexasaccharide without the GlcNS3S6S residue (compound 7* ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, the impact of 3- O -sulfation on the conformation of neighboring IdoA2S residues was investigated. The conformational analysis was completed by NMR through measuring the three bond proton proton coupling constants ( 3 J H-H ) 30 . The 3- O -sulfation increases the population of 2 S O conformer of the IdoA2S residue in hexasaccharides (compound 1 to 3 , Table 1 and Fig 1A), compared to that of the IdoA2S residue in a hexasaccharide without the GlcNS3S6S residue (compound 7* ).…”
Section: Resultsmentioning
confidence: 99%
“…The X-ray crystal structure and NMR solution structure of the complex of AT and fondaparinux demonstrate that the IdoA2S residue is present in 2 S O conformation in the complex 3233 . We reported that an IdoA-containing 6-mer, where the IdoA2S residue was substituted with an IdoA residue displaying 2 S O conformation, exhibited anti-FXa activity 30 (Table 2). However, a GlcA2S-containing 6-mer, where the IdoA2S residue was substituted with a GlcA2S residue displaying 4 C 1 conformation, did not display anti-FXa activity 8 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations